A Critical Review of the Word Classification System - Razieh Gholaminejad (Asociación Colombiana de Profesores de Ingles, 2020)
In this reflective paper, we review the currently-used word classification system proposed by linguist Paul Nation (2013, 2015) and the position of the academic vocabulary in this system. Different lexical layers in this system are explained as well as the underlying assumptions. Then, taking a critical position, we raise a number of criticisms against three different aspects of Nation's classification. The first criticism involves the fact that the system has sacrificed function for form in developing the lexical layers. The second focuses on the problem of equating 'academic words' with Coxhead's (2000) Academic Word List (AWL) and 'high-frequency words' with West's (1953) General Service List (GSL). Finally, the system is criticized for the lack of an independent lexical layer for discipline-specific academic vocabulary by ignoring disciplinary variation at the level of academic words. The critical points raised in the paper can be useful for English for Academic Purposes (EAP) materials developers, teachers, test developers, and syllabus/curriculum designers.